Building up the availability system using microcontroller and RFID technology based on Disable Availability System (DAS) / Ain Afifi Abdul Kadir - Abdul Kadir, Ain Afifi (2013)
Some of them require special hearing aid dedicated to learn and the use of sign language will be included when they learn and study. When teachers want take the attendance, they need use papers or book to be marked and they also need to check the student one by one because he/she do not listen if teachers called name. The presence of paper is not user friendly environment and it is hard to keep a good period of time in the good condition as a record attendance for the teachers to ensure it. Usually, teacher and warden get an attendance manually using papers or record in book only. The main objective of this project is to implement an RFID monitoring system which student need to use their student identification card which contain tag when they want entrance from or exit to their hostel and when entered or record the attendance during the class. The students only scan their card and RFID reader will read tag in that card. After that, all information in this card automatically transfers to database server. From the database, the teachers can update, delete and view all record about students. This system using Agile Method. Furthermore, can reduce the burden of teachers should take daily student attendance and students who live in hostel do not have to fill out a form or book before they go out. From all result, it can reduce time and energy if use this system.